2023
DOI: 10.1371/journal.pntd.0010905
|View full text |Cite
|
Sign up to set email alerts
|

A whole blood intracellular cytokine assay optimised for field site studies demonstrates polyfunctionality of CD4+ T cells in acute scrub typhus

Abstract: Background Assessment of cellular immune responses by combining intracellular cytokine staining and immunophenotyping using flow cytometry enables the simultaneous measurement of T cell phenotype and effector function in response to pathogens and vaccines. The use of whole blood samples rather than peripheral blood mononuclear cells avoids both the need for immediate processing and loss of functional antigen presenting cells due to processing and cryopreservation. Using whole blood provides the possibility to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…These flow cytometric studies have confirmed and greatly expanded the findings reported in our recent studies with Karp-infected mice [21]. The activation of CD4 + T cells in infected mice is consistent with recent study of polyfunctional CD4 + T cells in the whole blood of scrub typhus patients [52]. More importantly, our study clearly revealed differential kinetics of cellular immune responses in the lungs during acute stages of infection with two Ot strains.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 91%
“…These flow cytometric studies have confirmed and greatly expanded the findings reported in our recent studies with Karp-infected mice [21]. The activation of CD4 + T cells in infected mice is consistent with recent study of polyfunctional CD4 + T cells in the whole blood of scrub typhus patients [52]. More importantly, our study clearly revealed differential kinetics of cellular immune responses in the lungs during acute stages of infection with two Ot strains.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 91%